2012
DOI: 10.1111/all.12027
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal protein kinase C zeta expression determines the neonatal TCell cytokine phenotype and predicts the development and severity of infant allergic disease

Abstract: The findings suggest a potential role for the use of PKCζ levels in cord blood T cells as a presymptomatic test to predict allergy risk in children, particularly offspring of allergic mothers, and that the basis of this relationship is related to cytokine patterns in mature T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…PKCζ expression in neonatal T-cells was analysed by Western blot assay as described previously [22,28]. Briefly, proteins were separated by SDS/PAGE (12% gel) and transferred to nitrocellulose membrane (Bio-Rad Laboratories, Gladesville, NSW, Australia).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…PKCζ expression in neonatal T-cells was analysed by Western blot assay as described previously [22,28]. Briefly, proteins were separated by SDS/PAGE (12% gel) and transferred to nitrocellulose membrane (Bio-Rad Laboratories, Gladesville, NSW, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…Human CB T-cells, including those which were deficient in PKCζ, were maturated as previously described using phytohaemagglutinin (PHA) and IL-2 [22,28]. Maturation was gauged by flow cytometry, measuring the expression of CD45RA and CD45RO using anti-CD45RA-APC, anti-CD45RO-PE, anti-CD3-FITC or isotype control mix (IgG2b-APC, IgG2a-PE and IgG1-FITC) antibodies (all BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, two in vitro studies conducted in cells from SLE patients demonstrated induction of hypomethylation in CD4+ lymphocytes by UVB, suggesting a possible epigenetic mechanism (Li et al, 2010; Wu et al, 2013). T-cell expression of the gene containing our top methylation finding, PRKCZ , has been prospectively linked to infant allergic disease, highlighting its relevance to immune phenotypes (D’Vaz et al, 2012). Taken together, these studies imbue our preliminary findings in CD4+ lymphocytes with biological plausibility and stress the importance of future replication studies conducted in the same cell type.…”
Section: Discussionmentioning
confidence: 99%